In a biogas power plant from waste heat power generation system using Organic Rankine Cycle and multi-criteria optimization - Varis, Cagatay; Ozkilic, Selin Ozcira (ELSEVIER, 2023)
Increasing energy consumption, rapid population growth, and technological developments have increased the need for energy demand day by day. At the point of meeting this need, renewable energy is an important alternative resource that can replace rapidly exhaustible fossil fuels. There are many renewable energy sources such as sun, wind, hydrogen, geothermal, and biogas. Biogas, one of the most important renewable energy sources, is mainly used as fuel in combined heat -power (CHP) engines/gas engines and transformed into electrical energy. However, the effi-ciency of these engines is low owing to the fact that a considerable amount of the energy that enters with the combustion of biogas is thrown into the atmosphere as exhaust gas. In this context, the recovery of the waste heat of 26 gas engines with a temperature of 475-500 degrees C in the Silivri region of Istanbul and producing biogas from household wastes was studied. Calculate the waste heat values according to the exhaust gas flow, temperature, and pressure values to be taken from the chimney outlet of the gas engines in the facility. Subsequently, the determination of the parameters of the ORC (Organic Rankine Cycle) and the optimum consumption values of the equipment in the whole system in the loop as well as the optimum ORC mechanical power will help manage and optimize the electricity production.
Keywords: Electricity generation from waste heat; Waste heat recovery; ORC; Biogas; Gas engine; Energy production; Economic outputs; MULTIOBJECTIVE OPTIMIZATION; COGENERATION PLANT; ORC SYSTEMS; BIOMASS; RECOVERY; PERFORMANCE; DESIGN; GASIFIER; UNIT; Thermodynamics